PRE-SERVICE TEACHERS’ CLASSROOM CONFLICT MANAGEMENT SKILL IN YOGYAKARTA - Zulfa Inayah (FPB PBI 16 UMY 009, 2016)
Pre-service teachers are struggling from classroom conflict management. They declared that they are poor prepared in managing the classroom conflicts. This research aimed to analyse the classroom conflicts found by pre-service teachers and their strategies to manage those classroom conflicts. The research design applied by the researcher was qualitative research, which used one-on-one interview. The researcher interviewed three pre-service teachers of EED UMY from batch 2010, 2011, and 2012. Recorded audio of the interviews was being transcribed into the text for the data analysis. The method used in the data analysis was coding. In coding, the transcript was categorized into same themes related to the study. This research discovered the classroom conflicts faced by pre-service teachers and the strategies applied on classroom conflict management. There are eight classroom conflicts found by the pre-service teachers. Based on those conflicts, pre-service teachers have been able to applied several strategies to manage the conflicts. This is shown that pre-service teachers had enough knowledge in classroom management. Keywords: pre-service teachers, classroom conflicts, classroom conflict management, EED UMY